Transcriptomic and metabolomic analyses reveal the mechanism of color difference between two kinds of Cistanche deserticola before and after drying - Zhu, Tiantian; Zhang, Jing; Liu, Tianle; Zhang, Shuai; Yang, Baimei; Xu, Li; Zhao, Lei; Li, Mengfei; Jin, Ling (Frontiers in Plant Science, 2025)
IntroductionCistanche deserticola is an important traditional Chinese herbal medicine. The fresh cistanche squamous stem is typically yellow-white and brown after drying. Oil cistanche is a cistanche variant with a purple squamous stem that turns black after drying. The color difference between oil cistanche and cistanche is obvious, and the former has a higher market price. However, the mechanism underlying the color difference of oil cistanche and cistanche remains unclear.MethodsThis study evaluated the total flavone contents in oil cistanche and cistanche and compared the differential metabolites and differentially expressed genes (DEGs) and the contents of iridoid of dried oil cistanche and cistanche samples were determined by high-performance liquid chromatography, and finally the polysaccharides contents of them were determined to comprehensively analyze the formation mechanism of color difference between oil cistanche and cistanche.ResultsThe results showed that the total flavonoid content in oil cistanche was significantly higher than that in cistanche. Metabolomic analysis identified 50 differentially accumulated metabolites (DAMs) (34 up-regulated and 16 down-regulated), including carbohydrates, terpenoids, and flavonoids. Moreover, 3,376 DEGs were selected, among which significant up-regulated of IGS1 and CYP84A1 and down-regulated of 4CLL1, F6H2-2-1 and 5MAT1 genes jointly regulated flavonoid biosynthesis and affected the accumulation of differentially accumulated metabolites. Significant up-regulated of the CCD7 gene affected carotenoid component production, and significant up-regulated of the UGT85A24 gene promoted the accumulation of geniposidic acid. In addition, the contents of iridoid and polysaccharide in oil cistanche were significantly higher than those in cistanche.DiscussionThe differential expression of flavonoids and terpenoid differential metabolites and CYP84A1, 5MAT1, FLS, UGT85A24 and CCD7 mainly caused the purple color of fresh oil cistanche. Dried samples of oil cistanche were darker in color than those of cistanche, due to the higher content of iridoids and polysaccharides in the former. This study preliminarily revealed the causes of the color differences between oil cistanche and cistanche, and provided references for the systematic study of cistanche and its germplasm resources, as well as for the breeding of C. deserticola.